Carcass characteristics, palatability, and shelf life of beef finished on selected feeding regimes - Dell M. Allen; Melvin C. Hunt; Donald H. Kropf; V. Chen; O. Corte; G.H. Gutowski; A.R. Harrison; C. Kuntapanit; J.D. Thomas; M.E. "Smith" McCurry (Kansas Agricultural Experiment Station Research Reports, 1978)
This report terminates a 3-year study and includes data from this past year. Previous results were reported in the 1976 and '77 Cattlemen's Day Report.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Carcass; Palatibility; Shelf life